THE MODEL OF COMPETITIVE GRADUATION AS PART OF A DISTANCE LEARNING SYSTEM - Karpenko, M.; Shtelma, O.; Baranchuk, I. (Municipal economy of cities. Series: «Economy science», 2022)
The article deals with the use of process simulation modeling in distance education system. In particular, it proposes a generalized mathematical model of the behavior of an enterprise operating in a competitive market, and discusses one of the components of this model in detail. The generalized model is represented by a number of blocks, each of which is responsible for a particular production function of the enterprise. Among them are such blocks as "Production system", which transforms inputs into finished products; "Market" block, which implements a certain set of pricing rules (fixed, intended by producer or competitive) and forms demand and sales volumes taking into account consumer behavior; "Production development" block, which implements rules of production development depending on investment volumes, increasing funds, increasing technical and professional level; "Labor resources" block, which is responsible for the number of employees in the enterprise. All these components interact with each other, each of them has a set of adjustable parameters. Part of these parameters can be fixed, which allows you to get a set of local models, that is, consider the characteristics of the enterprise from different angles. In the paper, the basis was focused on working with a variant of the model called "Competitive output". According to the features of this model, the production function of the enterprise implements fixed mechanisms for calculating the volume of production, the dynamics of labor resources, labor force, the volume of investment. The main control parameter is the distribution of received resources between the consumption and development of the enterprise (carried out with the help of the normative). According to the entered values at each stage of modeling the system calculates the possible volumes of production, coordinates them with the demand, forms the current cost price of production taking into account technical level and characteristics of labor resources and thus offers the available volume of funds for further distribution. The purpose of working with the model is to reach the maximum level of consumption by means of rational allocation of resources with sustainable development of production up to the specified level. In the article the behavior of the Competitive Output model has been investigated and general recommendations on the choice of resource allocation strategy to achieve the optimal result have been given. The described model is implemented as a part of the remote system, which is used in teaching courses at the Kharkiv National University of Municipal Economy. Application of modeling tools in combination with traditional methods of e-learning has confirmed their high efficiency.